Annual Editions - Maidment, Fred (McGraw-Hill Higher Education, 2009)
Presents articles on the topic of International Business. This title features: an annotated listing of selected World Wide Web sites; an annotated table of contents; a topic guide; a general introduction; brief overviews for each section; a topical index; and, an online instructor's resource guide with testing materials